Method for testing mineral powder content in extracted and recycled old asphalt based on AFM technology

AFM technology analyzes the surface roughness of old asphalt, and solves the problem of low accuracy of mineral powder content detection in the existing technology, and realizes high-precision testing when the asphalt and mineral powder types are unknown. It is suitable for old asphalt in the field of road engineering Recycling of materials, simplifying detection steps and improving accuracy.

CN119269776APending Publication Date: 2025-01-075TH ENGINEERING LTD OF THE FIRST HIGHWAY ENGINEERING BUREAU CCCC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411485444.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When detecting the ore powder content in old bitumen after extraction and recovery, the prior art has low accuracy and cumbersome steps, making it difficult to achieve high-precision testing when the asphalt and ore powder type are unknown, affecting the performance design of the recycled mixture.

Method used

Using AFM technology, the surface roughness index of old asphalt after extraction and recovery is analyzed, and the corresponding relationship between asphalt surface roughness and ore powder content is used to calculate the ore powder content. The specific steps include preparing atomic force microscope observation samples, stirring and Determine the surface roughness and calculate the percentage content of ore powder.

Benefits of technology

It realizes high-precision testing of the mineral powder content in old asphalt when the types of asphalt and mineral powder are unknown. The test accuracy is high, the steps are simple and the application is convenient, and it is suitable for various old asphalt recycling materials in the field of road engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for testing the content of mineral powder in extracted and recycled old asphalt based on an AFM technology, and relates to the technical field of road engineering. The method comprises the following steps: 1, preparing an atomic force microscope observation sample; 2, observing the asphalt sample by using an atomic force microscope technology to obtain a nanoscale morphology graph, and measuring and analyzing the surface roughness of the asphalt sample; and 3, calculating the content of the mineral powder in the extracted and recycled old asphalt according to the corresponding relation between the asphalt surface roughness and the mineral powder content. According to the method, the testing process of the content of the mineral powder in the extracted and recycled asphalt is simplified, the accuracy of testing the content of the mineral powder in the extracted and recycled asphalt is improved, and help is provided for design of a regenerated mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road engineering, and in particular to a method for testing the mineral powder content in old asphalt after extraction and recovery based on AFM technology. Background Art

[0002] In the field of road engineering, the recycling and application of waste asphalt pavement materials has become a research hotspot. In the design stage of recycled mixtures, it is necessary to evaluate the performance of the old asphalt used in the recycled asphalt mixture (RAP). In this process, the old asphalt needs to be extracted and recycled first, but many studies have shown that there will still be some mineral powder residue in the old asphalt after extraction and recycling. This part of the mineral powder residue will affect the performance evaluation of the asphalt, so that the performance of the designed recycled asphalt mixture (RAP) cannot meet expectations. Therefore, it is very important to accurately test the content of mineral powder in the old asphalt after extraction and recycling.

[0003] At present, in practical applications, centrifugal extraction and Absen recovery methods are the most popular in China. The above methods mostly rely on conversion to calculate the content of mineral powder in the asphalt after extraction and recovery. The test results obtained are of poor accuracy, resulting in the performance of the designed recycled mixture still failing to meet expectations. Chinese patent CN101294950B discloses a method and device for detecting the content of mineral powder in asphalt mixture. The patent collects images of asphalt mortar through a digital camera, and uses the grayscale mean, grayscale deviation and grayscale median of the image as evaluation indicators to achieve the test of the content of asphalt mineral powder in the mixture; this method requires the types of mineral powder and asphalt to be known when applied, but in practical applications, the content of asphalt and mineral powder is often unknown, making it difficult to promote it to actual projects on a large scale. Chinese patent CN108106976A discloses a method for determining the composition and content of residual mineral powder during asphalt mixture extraction. The patent uses a laser particle size analyzer to compare the particle composition and distribution of the original mineral powder and the mineral powder without residual mineral powder after extraction, and determines the composition of the residual mineral powder by the difference in the particle composition of the two. The content of the residual mineral powder is calculated by the integral of the difference in the particle distribution of the two. When determining the particle composition and distribution of the mineral powder, each sample is tested for more than 3 groups of data, and the average value is taken as the final result. Four groups of data are preferably used to automatically generate average data to reduce the impact of data fluctuations. The detection steps are complicated, and the sample test data is large, which is relatively cumbersome in practical applications. Chinese patent CN103630459A discloses a method for testing asphalt content in asphalt mixture. The patent calculates the mass of mineral powder in the separated extract by the percentage content of mineral powder. The method is a centrifugal separation method, and the error is reduced by repeated weighing during the experiment. The detection steps are cumbersome. The test state of the separator must be kept consistent during the test. Different tightness of the screws will lead to different residual mineral powder content, which affects the test results. The calculation error range is large, the test results have large fluctuations, and the relative accuracy is low and the stability is poor. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention proposes a method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology. By analyzing the surface roughness index of the old asphalt after extraction and recovery using atomic force microscopy technology, the purpose of high-precision testing of the mineral powder content in the old asphalt after extraction and recovery can be achieved when the types of asphalt and mineral powder are unknown, thereby solving the shortcomings of the prior art.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology includes the following steps: Prepare samples for atomic force microscopy observation; Atomic force microscopy was used to observe asphalt samples, obtain nanoscale morphology, and measure and analyze the surface roughness of asphalt samples. The corresponding relationship between the surface roughness of asphalt and its mineral powder content is used to calculate the mineral powder content in the old asphalt after extraction and recovery, specifically:

[0006] In the formula, R q represents the roughness of the extracted and recovered asphalt surface, nm; x represents the mineral powder content in the extracted and recovered asphalt, %; A=0.658, C=3.356.

[0007] Furthermore, the preparation of the atomic force microscope observation sample is specifically as follows: The extracted and recycled old asphalt is heated and melted into a liquid state; Mixing asphalt using a mixer; Weigh the asphalt and pour it into the sample dish; Prepare a cap of appropriate size and cover it on the sample dish; Place the sample dish in the film heating oven and start the transmission mechanism to make the turntable rotate horizontally; After the sample surface is naturally leveled, place the sample dish containing asphalt in a 20°C environmental box for testing.

[0008] Preferably, the time interval between sample preparation and testing is no more than 2 days. When the time interval exceeds two days, the topography of the sample will change, and the surface of the topography will be blurred without obvious honeycomb structure.

[0009] Preferably, the asphalt heating temperature is set to 185°C.

[0010] Preferably, the mixer stirs the asphalt at 185° C. for 1 min.

[0011] Preferably, the film heating oven turntable rotates at a speed of 5.5 r / min, the rotation time is 5 minutes, and the oven temperature is set to 155°C.

[0012] Preferably, when observing the asphalt sample, the selected test temperature is 20°C; the selected test mode is AFM PF-QNM mode; the selected test parameters are peak force threshold 12nN, PFT gain: 25, scanning size 10μm, scanning rate 0.905Hz; the nanoscale morphology image is analyzed by Nanoscope Analysis software.

[0013] Preferably, the observed asphalt sample type is base asphalt or modified asphalt.

[0014] The present invention provides a method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology. First, the test method is applicable to various common old asphalt recycling materials in the field of road engineering, and has strong applicability to asphalt and mineral powder types. It can achieve the purpose of high-precision testing of the mineral powder content in the old asphalt when the types of asphalt and mineral powder are unknown. Secondly, the test method is based on high-resolution atomic force microscopy technology to establish a relationship between the surface roughness of the asphalt mixture and the mineral powder content. After repeated verification tests, it is shown that the relationship is highly accurate, the test accuracy is high, the test effect is good, and it is easy to use. Finally, the test method can directly measure the mineral powder content in the asphalt without separating the components of the asphalt mixture. The number of test samples is small, the steps are simple, the test speed is fast, and the test accuracy and stability are good. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a nanoscale morphology image of the asphalt A1 of Example 1 under an atomic force microscope; Figure 2 This is a nanoscale morphology image of the A2 asphalt in Example 2 under an atomic force microscope; Figure 3 This is a nanoscale morphology image of the A3 asphalt in Example 3 under an atomic force microscope; Figure 4 This is the nanoscale morphology of the A4 asphalt in Example 3 under an atomic microscope. DETAILED DESCRIPTION

[0016] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The invention discloses a method for testing the mineral powder content in the old asphalt after extraction and recovery based on the AFM technology, wherein the method of the invention is applicable to both base asphalt and modified asphalt. Embodiment 1

[0018] The recycled old materials used in the test process of this embodiment are actual road milling recycled materials, the asphalt type is base asphalt, and the mineral powder type is unknown. The old asphalt is milled and recycled by an extraction recovery method to obtain the extracted and recycled old asphalt A1. The atomic force microscope model is a Dimension Icon atomic force microscope.

[0019] Step 1: Preparation of AFM samples of old asphalt A1 (101) The old asphalt A1 is placed in an oven, the oven temperature is set to 185°C, and the oven is heated until the old asphalt A1 melts into a flowing liquid.

[0020] (102) The melted old asphalt A1 was stirred using a mixer at 185°C for 1 min.

[0021] (103) After the stirring is completed, weigh 5 g of the stirred old asphalt A1 and quickly pour it into a sample dish. Prepare a cap of appropriate size and cover it on the sample dish.

[0022] (104) The sample dish is placed on the disc of the film heating oven, and the transmission mechanism rotates the turntable horizontally at a speed of 5.5 r / min, a rotation time of 5 minutes, and an oven temperature of 155°C. This process can avoid the influence of uneven distribution of mineral powder on the final result.

[0023] (105) After the sample surface is naturally leveled, place the sample dish containing the old asphalt A1 sample in a 20°C environmental chamber for observation.

[0024] Step 2: Determine the surface roughness of asphalt samples using atomic force microscopy (201) The prepared old asphalt A1 sample was observed using atomic force microscopy technology, and the morphology of the old asphalt A1 sample was scanned to obtain its nanoscale morphology.

[0025] (202) One day after the sample was prepared, the AFM PF-QNM mode was used at 20 °C and atmospheric pressure, with an RTESPA probe and test parameters of peak force threshold 12 nN, PFT gain 25, scan size 10 μm, and scan rate 0.905 Hz. The nanoscale morphology images are shown in Figure 2. Figure 1 shown.

[0026] (203) The surface roughness of the old asphalt A1 sample was determined by observing the nanoscopic morphology and quantitatively analyzing its characteristics. The surface of the old asphalt A1 sample was imaged three-dimensionally by the peak force tapping mode of the atomic force microscope to obtain a scanned image, which was analyzed by the Nanoscope Analysis 1.8 software. The analysis of the scanned image includes: removing the influence of the steps and unevenness on the particle surface in the scanned image on the surface roughness calculation.

[0027] After removing the steps, unevenness and interface boundaries on the particle surface from the scanned image, the particle product surface is divided into several areas as RMS calculation areas for RMS calculation; the root mean square roughness RMS is calculated using the following formula.

[0028]

[0029] Where A is the size of the AFM scanning area and h0 is the reference height, which is defined as:

[0030] The surface roughness R of old asphalt A1 is obtained through the above analysis. q It is 6.6nm.

[0031] Step 3: Calculate the percentage of mineral powder (301) The mineral powder content in the old asphalt A1 was calculated by using the corresponding relationship between the surface roughness of the old asphalt A1 and its mineral powder content.

[0032] Among them, the corresponding relationship between asphalt surface roughness and its mineral powder content is:

[0033] In the formula, R q represents the roughness of the extracted and recovered asphalt surface, nm; x represents the mineral powder content in the extracted and recovered asphalt, %; A and C are fitting parameters. After fitting, A=0.658 and C=3.356.

[0034] (302) The surface roughness R of the old asphalt A1 q Substituting 6.6nm into the corresponding formula, we can get the mineral powder content x in the old asphalt A1 to be 4.9%. Embodiment 2

[0035] The method of Example 2 is the same as that of Example 1, except that the asphalt type is high-viscosity modified asphalt, the mineral powder type is unknown, and the old asphalt A2 is obtained by an extraction and recovery method.

[0036] Step 1: Preparation of AFM samples of old asphalt A2 (101) The old asphalt A2 is placed in an oven, the oven temperature is set to 185°C, and the oven is heated until the old asphalt A2 melts into a flowing liquid.

[0037] (102) The melted old asphalt A2 was stirred using a mixer at 185°C for 1 min.

[0038] (103) After the stirring is completed, weigh 5 g of the stirred old asphalt A2 and quickly pour it into a sample dish. Prepare a cap of appropriate size and cover it on the sample dish.

[0039] (104) The sample dish is placed on the disc of the film heating oven, and the transmission mechanism rotates the turntable horizontally at a speed of 5.5 r / min, a rotation time of 5 minutes, and an oven temperature of 155°C. This process can avoid the influence of uneven distribution of mineral powder on the final result.

[0040] (105) After the sample surface is naturally leveled, place the sample dish containing the old asphalt A2 sample in a 20°C environmental chamber for observation.

[0041] Step 2: Determine the surface roughness of asphalt samples using atomic force microscopy (201) The prepared old asphalt A2 sample was observed using atomic force microscopy technology, and the morphology of the old asphalt A2 sample was scanned to obtain its nanoscale morphology.

[0042] (202) Two days after the sample was prepared, the AFM PF-QNM mode was used at 20 °C and atmospheric pressure. The test parameters were peak force threshold 12 nN, PFT gain 25, scan size 10 μm, and scan rate 0.905 Hz. The nanoscale morphology images were obtained as shown in Figure 2. Figure 2 shown.

[0043] (203) The surface roughness of the old asphalt A2 was determined by observing the nanoscopic morphology and quantitatively analyzing its characteristics. The surface of the old asphalt A2 sample was imaged three-dimensionally by the peak force tapping mode of the atomic force microscope to obtain a scanned image, which was analyzed by the Nanoscope Analysis 1.8 software. The analysis of the scanned image includes: removing the influence of the steps and unevenness on the particle surface in the scanned image on the surface roughness calculation.

[0044] After removing the steps, unevenness, and interface boundaries on the particle surface from the scanned image, the surface of the particle product is divided into several areas as RMS calculation areas for RMS calculation; the root mean square roughness RMS is calculated using a formula, and the formula and calculation process are consistent with those in the embodiment. For detailed formulas and calculation processes, see Embodiment 1.

[0045] The surface roughness R of old asphalt A2 was obtained by analysis q It is 6.8nm.

[0046] Step 3: Calculate the percentage of mineral powder (301) The mineral powder content in the old asphalt A2 is calculated using the corresponding relationship between the surface roughness of the old asphalt A2 and its mineral powder content. For the detailed formula and calculation process, see Example 1.

[0047] (302) The surface roughness R of the old asphalt A2 q Substituting 6.8nm into the corresponding formula, we can get the mineral powder content x in the old asphalt A2 as 5.2%. Embodiment 3

[0048] The method of Example 3 is the same as that of Example 1, except that the type of asphalt used as the test material in the test process of this example is unknown, 4% mineral material is added to the recycled asphalt, and the old asphalt A3 is obtained by extraction and recovery.

[0049] Step 1: Preparation of AFM samples of old asphalt A3 (101) The old asphalt A3 is placed in an oven, the oven temperature is set to 185°C, and the oven is heated until the old asphalt A3 melts into a flowing liquid.

[0050] (102) The melted old asphalt A3 was stirred using a mixer at 185°C for 1 min.

[0051] (103) After the stirring is completed, weigh 5 g of the stirred old asphalt A3 and quickly pour it into a sample dish. Prepare a cap of appropriate size and cover it on the sample dish.

[0052] (104) The sample dish is placed on the disc of the film heating oven, and the transmission mechanism rotates the turntable horizontally at a speed of 5.5 r / min, a rotation time of 5 minutes, and an oven temperature of 155°C. This process can avoid the influence of uneven distribution of mineral powder on the final result.

[0053] (105) After the sample surface is naturally leveled, the sample dish containing the old asphalt A3 sample is placed in a 20°C environmental chamber for observation.

[0054] Step 2: Determine the surface roughness of asphalt samples using atomic force microscopy (201) The prepared old asphalt A3 sample was observed using atomic force microscopy technology, and the morphology of the old asphalt A3 sample was scanned to obtain its nanoscale morphology.

[0055] (202) One day after the sample was prepared, the AFM PF-QNM mode was used at 20 °C and atmospheric pressure. The test parameters were peak force threshold 12 nN, PFT gain 25, scan size 10 μm, and scan rate 0.905 Hz. The nanoscale morphology images were obtained as shown in Figure 2. Figure 3 shown.

[0056] (203) The surface roughness of the old asphalt A3 was determined by observing the nanoscopic morphology and quantitatively analyzing its characteristics. The surface of the old asphalt A3 sample was imaged in three dimensions by the peak force tapping mode of the atomic force microscope to obtain a scanned image, which was analyzed by the Nanoscope Analysis 1.8 software. The analysis of the scanned image includes: removing the influence of the steps and unevenness on the particle surface in the scanned image on the surface roughness calculation.

[0057] After removing the steps, unevenness, and interface boundaries on the particle surface from the scanned image, the surface of the particle product is divided into several areas as RMS calculation areas for RMS calculation; the root mean square roughness RMS is calculated using a formula, and the formula and calculation process are consistent with those in the embodiment. For detailed formulas and calculation processes, see Embodiment 1.

[0058] The surface roughness R of old asphalt A3 is obtained through the above analysis. q It is 8.1nm.

[0059] Step 3: Calculate the percentage of mineral powder (301) The mineral powder content in the old asphalt A3 is calculated using the corresponding relationship between the surface roughness of the old asphalt A3 and its mineral powder content. For the detailed formula and calculation process, see Example 1.

[0060] (302) The surface roughness R of the old asphalt A3 q Substituting 8.1 nm into the corresponding formula, we can obtain the mineral powder content x in the old asphalt A3 as 7.2%. Embodiment 4

[0061] The method of Example 4 is the same as that of Example 1, except that the test materials used in the test process of this example are known data, and 3% limestone powder is added to the base asphalt to obtain asphalt A4.

[0062] Step 1: Preparation of AFM samples of asphalt A4 (101) Asphalt A4 is placed in an oven, the oven temperature is set to 185 °C, and the oven is heated until the asphalt A4 melts into a flowing liquid.

[0063] (102) The melted asphalt A4 was stirred using a stirrer at 185 °C for 1 min.

[0064] (103) After the stirring is completed, weigh 5 g of the stirred asphalt A4 and quickly pour it into a sample dish. Prepare a cap of appropriate size and cover it on the sample dish.

[0065] (104) The sample dish is placed on the disc of the film heating oven, and the transmission mechanism rotates the turntable horizontally at a speed of 5.5 r / min, a rotation time of 5 minutes, and an oven temperature of 155°C. This process can avoid the influence of uneven distribution of mineral powder on the final result.

[0066] (105) After the sample surface is naturally leveled, the sample dish containing the asphalt A4 sample is placed in a 20°C environmental chamber for observation.

[0067] Step 2: Determine the surface roughness of asphalt samples using atomic force microscopy (201) The prepared asphalt A4 sample was observed using atomic force microscopy technology, and the morphology of the asphalt A4 sample was scanned to obtain its nanoscale morphology.

[0068] (202) One day after the sample was prepared, the AFM PF-QNM mode was used at 20 °C and atmospheric pressure. The test parameters were peak force threshold 12 nN, PFT gain 25, scan size 10 μm, and scan rate 0.905 Hz. The nanoscale morphology images were obtained as shown in Figure 2. Figure 4 shown.

[0069] (203) The surface roughness of asphalt A4 was determined by observing the nanoscopic morphology and quantitatively analyzing its features. The surface of the asphalt A4 sample was imaged in three dimensions using the peak force tapping mode of an atomic force microscope to obtain a scanned image, which was analyzed using Nanoscope Analysis 1.8 software. The analysis of the scanned image included removing the influence of the steps and unevenness on the particle surface in the scanned image on the surface roughness calculation.

[0070] After removing the steps, unevenness, and interface boundaries on the particle surface from the scanned image, the surface of the particle product is divided into several areas as RMS calculation areas for RMS calculation; the root mean square roughness RMS is calculated using a formula, and the formula and calculation process are consistent with those in the embodiment. For detailed formulas and calculation processes, see Embodiment 1.

[0071] The surface roughness R of asphalt A4 is obtained through the above analysis. q It is 4.9nm.

[0072] Step 3: Calculate the percentage of mineral powder (301) The mineral powder content in asphalt A4 is calculated using the corresponding relationship between the surface roughness of asphalt A4 and its mineral powder content. For the detailed formula and calculation process, see Example 1.

[0073] (302) The surface roughness R of asphalt A4 q Substituting 4.9 nm into the corresponding formula, we can obtain the mineral powder content x in asphalt A4 as 2.4%. Comparative Example

[0074] In order to make the experimental results more comparable, ensure the accuracy of the content of mineral powder in the recovered asphalt observed by atomic force microscopy technology in this embodiment and increase the persuasiveness, the recovered old asphalt samples A1, A2, A3, A4 used in the test process were respectively detected by centrifugal extraction to detect the mineral powder content in A1, A2, A3, A4, and compared with the results of this embodiment. The obtained data are shown in Table 1. According to the data in Table 1, it can be seen that the mineral powder content tested by the prior art is similar to the content tested by the technical solution of the present invention, which can illustrate the authenticity and accuracy of the technical solution of the present invention;

[0075] It can be seen from the above embodiments that the method provided by the present invention for testing the mineral powder content in the extracted and recovered old asphalt based on AFM technology has simple steps, is easy to implement, and the test results are more accurate than those of the prior art, and has broad application prospects.

[0076] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology, characterized in that: The following steps are involved: Prepare samples for atomic force microscopy observation; Atomic force microscopy was used to observe asphalt samples, obtain nanoscale morphology, and measure and analyze the surface roughness of asphalt samples. The corresponding relationship between the surface roughness of asphalt and its mineral powder content is used to calculate the mineral powder content in the old asphalt after extraction and recovery, specifically: , where R q represents the roughness of the extracted and recovered asphalt surface, nm; x represents the mineral powder content in the extracted and recovered asphalt, %; A=0.658, C=3.

356.

2. The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology according to claim 1 is characterized in that: The preparation of the atomic force microscope observation sample is specifically as follows: The extracted and recycled old asphalt is heated and melted into a liquid state; Mixing asphalt using a mixer; Weigh the asphalt and pour it into the sample dish; Place the sample dish in the film heating oven and start the transmission mechanism to make the turntable rotate horizontally; After the sample surface is naturally leveled, place the sample dish containing asphalt in a 20°C environmental box for testing.

3. The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology according to claim 2 is characterized in that: The time interval between sample preparation and testing shall not exceed 2 days.

4. The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology according to claim 2 is characterized in that: The asphalt heating temperature was set to 185°C.

5. The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology according to claim 2 is characterized in that: The mixer stirs the asphalt at 185° C. for 1 min.

6. The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology according to claim 2 is characterized in that: The film heating oven turntable rotates at a speed of 5.5 r / min, the rotation time is 5 minutes, and the oven temperature is set at 155°C.

7. The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology according to claim 1 is characterized in that: When observing the asphalt sample, the selected test temperature is 20°C; the selected test mode is AFM PF-QNM mode; the selected test parameters are peak force threshold 12nN, PFTgain25, scanning size 10μm, scanning rate 0.905Hz; the nanoscale morphology image is analyzed by software.

8. The method for testing the mineral powder content in the old asphalt after extraction and recovery based on AFM technology according to claim 1 is characterized in that: The asphalt sample type is base asphalt or modified asphalt.

Citation Information

Patent Citations

  • Method and device for detecting powdered ore content in asphalt mixture

    CN101294950B

  • Method used for detecting asphalt content of asphalt mixtures

    CN103630459A

  • Method for determining composition and content of residual mineral powder in extraction process of asphalt mixture

    CN108106976A